Γνωρίζοντας το Κυπριακό Μουσείο μέσα από νέες εμπειρίες - Λοφίτου, Φάνη (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2018)
The present review aimed at finding an entertaining medium that would make children's experience more interesting within a historical museum such as the Cyprus Museum. When researching the museum, it was noted that the presence of technology was largely absent. Thus, the decision for creating an application that combines entertainment with the factor of education was taken. The design and content of the application was evaluated by some members of the museum’s staff and teachers, some with specialty in museum studies. For the purpose of this research, the application did not come into operation but remained in a prototype form since the function was not being tested in this case. The application consists of 14 tasks, as are the museum's halls. Each task, based on the room’s content, has a game feeling to it since some of them are indeed influenced by existing games such as crosswords, mix and match games, interactive children's books etc. The application also includes basic information about each room or period, depending on its content, the map of the museum and a QR scanner that offers a more interactive experience with the space for those who wish it.
Keywords: children, museum, interactive application, interactive education; παιδιά, µουσείο, δια δραστική εφαρµογή, δια δραστική εκµάθηση